La transferencia: de la suposición a lo no domesticado The transference: from the supposition to the not domesticated - David Laznik; Elena Lubián (Anuario de Investigaciones, 2005)
La constitución de la Neurosis de Transferencia supone dos dimensiones: una que atañe al saber y, un movimiento de investidura libidinal que comporta al campo de la pulsión. La problemática delimitada apunta a interrogar desde qué coordenadas podemos operar cuando lo que comanda la escena es un movimiento libidinal que no se ordena respecto del despliegue de la cadena significante. The constitution of the Neurosis of Transfer supposes two dimensions: one that involves to the field of to know. Other one, a movement of investiture libidinal relative to the field of the Drive. The exposed problem points to know how we can operate when what commands the scene it is a movement libidinal that does not arrange itself respect of the unfolding of the significant Caín.